2010
DOI: 10.1074/jbc.m110.119321
|View full text |Cite
|
Sign up to set email alerts
|

The Protein-disulfide Isomerase DsbC Cooperates with SurA and DsbA in the Assembly of the Essential β-Barrel Protein LptD

Abstract: The assembly of the ␤-barrel proteins present in the outer membrane (OM) of Gram-negative bacteria is poorly characterized. After translocation across the inner membrane, unfolded ␤-barrel proteins are escorted across the periplasm by chaperones that reside within this compartment. Two partially redundant chaperones, SurA and Skp, are considered to transport the bulk mass of ␤-barrel proteins. We found that the periplasmic disulfide isomerase DsbC cooperates with SurA and the thiol oxidase DsbA in the folding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 33 publications
0
52
0
1
Order By: Relevance
“…The association of LptD with its partner, LptE (4), and/or the isomerase activity of DsbC (15), rearranges this disulfide such that Cys 173 now becomes bonded to the fourth cysteine (Cys 725 ) to make the 2-4 disulfide bond. At this point, DsbA reengages LptD to catalyze a second disulfide bond between the remaining cysteines (Cys 31 and Cys 724 ), resulting in the 1-3 disulfide bond (16).…”
Section: Resultsmentioning
confidence: 99%
“…The association of LptD with its partner, LptE (4), and/or the isomerase activity of DsbC (15), rearranges this disulfide such that Cys 173 now becomes bonded to the fourth cysteine (Cys 725 ) to make the 2-4 disulfide bond. At this point, DsbA reengages LptD to catalyze a second disulfide bond between the remaining cysteines (Cys 31 and Cys 724 ), resulting in the 1-3 disulfide bond (16).…”
Section: Resultsmentioning
confidence: 99%
“…These reducing equivalents maintain DsbC in a reduced state in the periplasm, allowing the protein to function as an isomerase/reductase (see below). Several DsbC substrates with multiple cysteines have already been identified; they include four periplasmic enzymes (42,43) as well as the essential ␤-barrel protein LptD (44). The presence of two disulfides formed between cysteines that are not consecutive in the sequence of RcsF suggested that the assembly of this protein involves DsbC.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis with a DsbA mutant that forms kinetically stable mixed-disulfide intermediates with substrates suggested that DsbA is involved in formation of both nonnative and native disulfide bonds in LptD (17). A previous study also suggested that DsbC participates in the oxidative folding of LptD (17,20) although disruption of the dsbC gene had little effect on the stability of LptD (19).…”
mentioning
confidence: 94%